Sources and Outcomes of Employee Engagement: A Qualitative Inquiry on Personnel Perception - Adhikari, Pralhad (New Trends in Psychology, 2022)
Objective: The aim of this study was to explore what caused employee engagement and what it caused in the workplace. Method: An open-ended survey was conducted among 42 employees with a set of 12 questions. A total of 504 responses have been analyzed in the framework of qualitative and conventional content analysis. Results: Three concepts emerged as sources of employee engagement: personal skills, good working conditions, and good human resource management. Two concepts emerged as its outcomes: personal outcomes and organizational consequences. A new theme, besides causes and consequences, also came up: barriers to engagement. Conclusion: The conclusion is that Nepalese employees can be engaged at the workplace if their needs are met, if the working condition is made safe, and if they themselves learn skills to adapt, communicate and work well. Consequently, they can give more performance being satisfied at a job.